Preparation method and application of shrimp shell aerogel

The preparation of shrimp shell biochar and reduced graphene oxide composite aerogel solved the problem of poor adsorption effect of existing adsorption materials for diazepam, and realized efficient and stable treatment and resource utilization of water pollutants.

CN121314484APending Publication Date: 2026-01-13CHINESE ACAD OF FISHERY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511863805.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-11
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing adsorption materials have poor adsorption effect on diazepam, poor regenerability, insufficient mechanical strength, and unstable performance due to batch differences in raw materials, making it difficult to efficiently remove diazepam pollution from water bodies.

Method used

By preparing shrimp shell biochar and reduced graphene oxide composite aerogel, a highly efficient and reversible adsorption system was formed by adopting a porous structure and cross-linked network design, combining hydrophobic interactions and hydrogen bonding, and optimizing the freeze-drying process.

Benefits of technology

It significantly improved the adsorption capacity and selectivity for diazepam, enhanced mechanical stability and recycling performance, reduced production costs, and realized the resource utilization of waste and environmentally friendly pollutant treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121314484A_ABST
    Figure CN121314484A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of shrimp shell aerogel, and belongs to the technical field of shrimp shell aerogel preparation.The preparation method comprises the steps that shrimp shells are cleaned, dried and smashed, then heated to 400 DEG C in the oxygen atmosphere for pyrolysis and screened, and BC400 is obtained; the preparation method comprises the following steps: reacting graphene oxide with L-ascorbic acid at 80 DEG C for 90 minutes to prepare an rGO solution; performing vortex oscillation and ultrasonic treatment on the BC400 and the rGO solution to obtain a composite solution; pVA and a sodium citrate solution react under specific conditions to prepare a PVA / SC5: 1 solution; and mixing the composite solution with a PVA / SC solution, sequentially stirring, performing injection molding, freezing at-80 DEG C for 1 hour, and freeze-drying at-80 DEG C and 0.1 mbar for 16 hours. The prepared shrimp shell aerogel has a more developed pore structure and richer surface functional groups, can form a powerful effect with diazepam molecules, improves the adsorption efficiency and selectivity, greatly improves the cycle stability through optimization of an adsorption mechanism, and has a good application prospect. The problems that an existing adsorption material is poor in diazepam adsorption effect and poor in reproducibility are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of shrimp shell aerogel preparation technology, specifically relating to a method for preparing shrimp shell aerogel and its application. Background Technology

[0002] While meeting domestic consumption and export demands, the seafood processing industry also generates a large amount of by-products. Shrimp shells, as the most significant waste product during processing, account for as much as 35%. – 40% of shrimp shells and other crustacean processing byproducts are still disposed of through traditional landfill or incineration methods, with an annual output exceeding 2.5 million tons. This extensive treatment not only wastes valuable natural resources such as chitin, protein, and calcium carbonate, but also triggers a series of environmental problems. Landfill disposal occupies a large amount of land resources and easily generates leachate that pollutes soil and groundwater during natural degradation; incineration releases harmful gases, exacerbating air pollution and placing a heavy burden on the ecological environment. Therefore, how to achieve the resource-efficient utilization of shrimp shells and other crustacean processing waste has become a critical issue that urgently needs to be addressed in the green transformation of the aquatic product processing industry and environmental protection. In recent years, waste resource utilization technologies have been continuously developing, among which pyrolysis technology provides an effective pathway for the high-value transformation of shrimp shells. Studies have shown that organic materials can be prepared through the pyrolysis of shrimp and crab shells. Inorganic composite biochar, due to its unique pore structure, abundant surface functional groups, and good chemical stability, significantly enhances its adsorption capacity for polar organic pollutants, thereby enabling the immobilization and resource recovery of processing waste. Compared with traditional commercial activated carbon, the production cost of shrimp shell biochar can be reduced by 40%. –With a purity of 55%, and its raw materials being widely available and inexpensive, it typically requires only simple washing and drying with minimal pretreatment steps for preparation, fully aligning with the core principles of the circular economy: "reduction, reuse, and resource recovery." In-situ conversion of such waste into functional biochar materials for application in pollutant treatment not only solves the disposal problem of aquatic processing waste but also achieves synergistic integration of solid waste treatment and in-situ pollution control in aquaculture systems, yielding significant economic and environmental benefits. Aerogels, as porous materials with a three-dimensional network structure, possess unique advantages such as large specific surface area, high porosity, adjustable pore size, and abundant surface active sites, showing broad application prospects in adsorption, catalysis, and energy storage. Compared to traditional adsorption materials, aerogels, with their ultra-large specific surface area and abundant pore structure, can provide more adsorption sites for target pollutants, significantly improving adsorption efficiency. Simultaneously, their unique chemical structure makes them easy to modify surface, allowing for targeted improvement in the adsorption selectivity for specific pollutants. Aerogels prepared from shrimp shells can achieve a balance between high adsorption performance and good biodegradability by utilizing the natural functional groups of chitin / chitosan, significantly reducing raw material costs and waste emissions, aligning with the concepts of green chemistry and circular economy. However, existing research mainly focuses on the adsorption of heavy metals and conventional organic pollutants by aerogels, while systematic research on antibiotics targeting the nervous system remains relatively limited. Diazepam, a benzodiazepine sedative-hypnotic drug used in the nervous system, is widely used in clinical medicine due to its sedative, anti-anxiety, and anticonvulsant effects. However, in recent years, the abuse of diazepam in non-medical fields has become increasingly prominent, especially in fishing activities, where some anglers add diazepam to their bait to increase their catch. Once diazepam enters the water through bait, it is difficult to degrade naturally and accumulates continuously. This not only severely damages the nervous and reproductive systems of aquatic organisms such as fish and crustaceans, leading to abnormal behavior, decreased reproductive capacity, and disruption of the aquatic ecosystem, but it can also enter the human body through biomagnification in the food chain. Long-term intake may cause adverse reactions such as drowsiness, dizziness, and fatigue, and may even affect the function of organs such as the liver and kidneys, posing a potential threat to human health. Currently, methods for treating diazepam in water mainly include advanced oxidation, biodegradation, and adsorption. While advanced oxidation methods offer high treatment efficiency, they suffer from drawbacks such as high equipment investment, high operating costs, and the potential for secondary pollution. Biodegradation methods are subject to stringent environmental conditions, have long degradation cycles, and are ill-suited to complex aquatic environments. Adsorption methods, due to their simple operation, low treatment costs, and good adsorption effects, have become the preferred technology for treating low-concentration pharmaceutical pollutants in water. However, existing adsorption materials, such as commercial activated carbon and zeolite, have limitations including limited adsorption capacity, poor selectivity, and difficulty in regeneration, making it difficult to meet the practical needs for efficient removal of diazepam from water. The main problems are as follows: (1) Insufficient adsorption selectivity and capacity: Traditional bio-based adsorbents exhibit low adsorption capacity and affinity for weakly polar and hydrophobic organic drugs such as diazepam. The surface of unmodified chitosan is rich in hydrophilic amino / hydroxyl groups, and in the aqueous phase, it mainly relies on non-specific van der Waals forces and hydrophobic interactions with target molecules. The hydrophilic groups cannot effectively form strong interactions with hydrophobic molecules. In addition, unsuitable specific surface area or pore size distribution also greatly limits molecule entry and residence time, thereby reducing the effective adsorption amount.

[0003] (2) Poor mechanical strength, easy collapse, and difficulty in large-scale drying: Ordinary biogels, especially after traditional freeze-drying / atmospheric pressure drying, often experience network structure collapse, reduced specific surface area and pore volume, leading to unstable performance. The preparation of aerogels to maintain a highly porous structure usually relies on costly and equipment-intensive processes such as solvent replacement or supercritical CO2 drying. If atmospheric pressure drying is used without surface reinforcement, surface tension will cause capillary collapse. In addition, insufficient crosslinking or a single crosslinking method will result in poor mechanical strength, making it unable to withstand subsequent processing and recycling operations.

[0004] (3) Lack of selective sites and poor regeneration performance: Existing materials have low regeneration efficiency and significant adsorption capacity decay. Single hydrophobic interactions are insufficient to achieve reversible and highly selective binding. The lack of chelating or inclusion structures means that adsorption and desorption require strong elution solvents or harsh conditions, reducing cycle stability.

[0005] (4) Raw material impurities, process repeatability and yield issues: When using natural shrimp shells for direct preparation, differences in raw materials from different batches will lead to differences in the performance of the final product. If the demineralization and deproteinization processes are not strictly controlled, impurities that affect gel nucleation and network formation will remain. In addition, the degree of deacetylation and the deacetylation rate have a direct impact on dissolution behavior and cross-linking reaction, and if they are not strictly controlled, batch consistency will be affected.

[0006] Therefore, it is urgent to develop new, efficient, and environmentally friendly adsorption materials. Summary of the Invention

[0007] The purpose of this invention is to address the problems of poor adsorption efficiency and poor regenerability of existing adsorption materials for diazepam. It provides a method for preparing shrimp shell aerogel and its application. Through process optimization, the prepared shrimp shell aerogel possesses a more developed pore structure and richer surface functional groups, enabling it to form a strong interaction with diazepam molecules, thereby improving adsorption efficiency and selectivity. This method is environmentally friendly, avoiding the use of toxic reagents. The material is biodegradable, posing no risk of secondary pollution. It provides a feasible technical approach for the resource utilization of aquatic processing waste and the control of drug pollution in the aquatic environment. Furthermore, it is of great significance for promoting the green and sustainable development of the aquatic processing industry and ensuring water quality and human health.

[0008] A method for preparing shrimp shell aerogel includes the following steps: (1) Preparation of shrimp shell biochar BC400: Shrimp shell biomass was washed, dried, pulverized, and transferred to a muffle furnace for pyrolysis modification to obtain biochar BC400. (2) In-situ reduction preparation of rGO solution: Graphene oxide and L-ascorbic acid were reacted at 78 °C. – The reaction was carried out at 82 °C for 90 min. After the reaction was completed, the product was cooled to room temperature to obtain a reduced graphene oxide (rGO) solution. (3) BC400 / rGO 4:1 Preparation of the composite solution: After mixing BC400 biochar powder with rGO solution, the mixture was subjected to vortexing at 2500 r / min for 5 min and ultrasonication at 100 Hz for 30 min to obtain a BC400 / rGO mixture with a biochar to reduced graphene oxide mass ratio of 4:1, which was uniformly and stably dispersed. 4:1 Composite solution; (4) PVA / SC5:1 Preparation of crosslinking solution: Polyvinyl alcohol (PVA) powder was dissolved in deionized water, and then a 10% (w / v) sodium citrate (SC) aqueous solution was added to react and obtain PVA / SC. 5:1 Cross-linked mixed solution; (5) Preparation of glutaraldehyde-GA crosslinking mixture: Mix 50% glutaraldehyde, methanol, glacial acetic acid, 98% concentrated sulfuric acid, and deionized water thoroughly and store in a brown glass bottle away from light. Use as an acidic catalytic crosslinking agent. (6) BC400 / rGO 4:1 @SBA Composite Shrimp Shell Aerogel Molding and Post-processing: BC400 / rGO 4:1 Composite solution with PVA / SC 5:1 The solutions were mixed, and then the acidic catalytic crosslinking agent mixture prepared in step (5) was added. The resulting crosslinking sol was stirred, molded, and frozen at -80℃ for 1 h. Then it was freeze-dried at -80℃ and 0.1 mbar for 16 h to obtain BC400 / rGO with a three-dimensional porous network structure. 4:1 @SBA Composite Shrimp Shell Aerogel.

[0009] Further, step (1) specifically involves: washing the shrimp shell biomass three times with distilled water, filtering out the water, drying it at 60 ℃ for 12 h, crushing the dried shrimp shell biomass and transferring the powdered biomass into a muffle furnace, raising the temperature of the muffle furnace from 30 ℃ to 400 ℃ at a heating rate of 10 ℃ / min under an oxygen atmosphere for pyrolysis modification, and holding it at that temperature for 120 min. After cooling, the resulting biochar is passed through a 200-mesh sieve and named BC400.

[0010] Further, step (2) specifically involves: weighing 0.3 g of graphene oxide and 0.3 g of L-ascorbic acid, dissolving them together in 30 mL of distilled water, reacting the mixed solution at 80 °C for 90 min, adding distilled water every 30 min during the reaction to maintain the total volume of the reaction system at 30 mL, and cooling the product to room temperature after the reaction to obtain a reduced graphene oxide rGO solution.

[0011] Further, step (3) specifically involves: weighing 1.2 g of the BC400 biochar powder prepared in step (1) and adding it to all the rGO solution in step (2). The mixture is placed in a 50 mL centrifuge tube and vortexed vertically at 2500 r / min for 5 min for initial dispersion. Subsequently, it is subjected to ultrasonic cell disruption at 100 Hz in a constant temperature water bath at 25 °C for 30 min to obtain a BC400 / rGO mixture with a biochar to reduced graphene oxide mass ratio of 4:1 that is uniformly and stably dispersed. 4:1 Composite solution.

[0012] Further, step (4) specifically involves: weighing 10.0 g of polyvinyl alcohol (PVA) powder, dissolving it in 200 mL of deionized water, and magnetically stirring at 400 rpm for 1 h in an 80 ℃ water bath until completely dissolved, obtaining a transparent viscous solution with a concentration of 50 g / L. After the solution cools to room temperature, add 20 mL of sodium citrate (SC) aqueous solution with a mass-volume concentration of 10% (w / v). Then, continue to magnetically stir the mixed solution at 400 rpm for 3 h at 60 ℃ to allow SC and PVA to react fully, obtaining PVA / SC. 5:1 Cross-linked mixed solution.

[0013] Further, the steps ( 5 Specifically, the following components are mixed in the following order by volume: 47.14 mL of 50% glutaraldehyde, 20 mL of methanol, 20 mL of glacial acetic acid, 2 mL of 98% concentrated sulfuric acid, and 150 mL of deionized water. After mixing evenly, the resulting solution is stored in a brown glass bottle away from light and used as an acidic catalytic crosslinking agent.

[0014] Further, step (6) specifically involves measuring 1.25 mL of BC400 / rGO. 4:1 The composite solution with 1.25 mL PVA / SC 5:1 The solution was mixed in a 10 mL beaker and stirred at 600 rpm for 2 min on a magnetic stirrer to form a uniform black sol. Then, 1.37 mL of the acidic catalytic crosslinking agent mixture prepared in step (5) was added to the sol, and stirring was continued at 600 rpm for 3 min to complete the crosslinking reaction. The resulting crosslinked sol was injected into a food-grade silicone mold and immediately placed in an ultra-low temperature freezer at -80 °C for 1 h to achieve physical freeze-thaw crosslinking and promote complete solidification. The solidified sample was then quickly transferred to a freeze dryer and freeze-dried at -80 °C and 0.1 mbar vacuum for 16 h to allow the ice crystal template to fully sublimate, finally obtaining BC400 / rGO with a three-dimensional porous network structure.4:1 @SBA Composite Shrimp Shell Aerogel.

[0015] An application of shrimp shell aerogel: BC400 / rGO with a three-dimensional porous network structure prepared according to the above preparation method. 4:1 Application of @SBA composite shrimp shell aerogel in diazepam adsorption.

[0016] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. Significantly improves the adsorption capacity and selectivity for diazepam: This invention prepares a highly efficient adsorption aerogel based on a composite of shrimp shell pyrolysis biochar and reduced graphene oxide (rGO). The preparation method includes combining porous biochar BC400 and reduced graphene oxide (rGO) at a mass ratio of 4:1, and constructing an aerogel with a hierarchical pore structure of micropores, mesopores, and macropores through a combined process of rapid freezing at -80 ℃ and vacuum freeze-drying at -80 ℃. The hydrogen bonding between the hydroxyl and carboxyl groups on the surface of BC400 and diazepam, as well as the hydrophobic interaction between the hydrophobic sheets of rGO and the aromatic rings of diazepam, synergistically enhance the adsorption performance and improve the adsorption capacity for diazepam. Furthermore, by introducing a polyvinyl alcohol / sodium citrate (PVA / SC, 5:1) composite matrix, the aerogel prevents aggregation by utilizing the hydrogen bonding between the SC hydroxyl groups and carbon materials, and regulates the hydrophilic-hydrophobic balance of the system, effectively suppressing interference from the aqueous environment and other organic impurities. This allows the aerogel to maintain an adsorption selectivity of over 85% for diazepam in complex water bodies, which is nearly twice that of traditional aerogels.

[0017] 2. Improved Pore Retention and Mechanical Stability of Aerogels: This invention effectively solves the problems of structural collapse and insufficient mechanical properties of bio-based aerogels during drying due to capillary forces by introducing a dual cross-linking mechanism and optimizing the freeze-drying process. Specifically, on the one hand, a stable chemical cross-linking network is constructed by utilizing the Schiff base reaction between glutaraldehyde and the hydroxyl groups of PVA molecular chains and the carboxyl groups on the BC400 / rGO surface. On the other hand, ultra-low temperature freezing at -80 ℃ promotes the formation of fine ice crystals from water. After the ice crystals sublimate, a three-dimensional porous structure is formed and fixed, thereby increasing the compressive strength of the aerogel to ≥0.3 MPa without the need for supercritical CO2 drying, which is 2 MPa higher than that of traditional freeze-dried gels. – The aerogel exhibits a three-fold increase in efficiency and excellent tolerance to cyclic operation. Furthermore, by precisely controlling freeze-drying parameters, such as a -80°C cold trap temperature, a 0.1 mbar vacuum, and a 16-hour freeze-drying time, a pore structure retention rate exceeding 90% is achieved while avoiding solvent displacement. This not only overcomes the capillary collapse problem caused by atmospheric pressure drying but also significantly reduces equipment costs and process complexity. In addition, the use of chemically stable and easily demolded food-grade silicone molds ensures the integrity of the aerogel structure and batch consistency, achieving a demolding success rate of over 90%, providing reliable support for large-scale production.

[0018] 3. Excellent Cyclic Regeneration Performance: This invention addresses the problems of existing adsorption materials such as commercial activated carbon and traditional biochar, which rely on a single physical adsorption mechanism, leading to the need for strong elution conditions such as high-concentration acids and alkalis for desorption, low regeneration efficiency, and significant capacity decay after multiple cycles. By optimizing the adsorption mechanism, a reversible adsorption system based on a complex of hydrophobic interactions and hydrogen bonds is constructed. This aerogel material only requires a low-concentration 20% methanol aqueous solution for desorption, and room temperature shaking for 30 minutes is sufficient to achieve a desorption efficiency of over 85%, avoiding damage to the material structure caused by strong eluents. After three adsorption / desorption cycles, its adsorption capacity for diazepam remains above 75%, 1.5 times higher than that of traditional activated carbon, and the material structure remains intact, thus significantly improving cycle stability, extending service life, and reducing the cost of consumables per water treatment cycle by 40%. – 50%.

[0019] 4. Resource and Environmental Benefits: This invention provides a method for preparing high-performance aerogels from shrimp shell waste, achieving a closed-loop resource utilization process of "waste – high-value-added materials – pollution control." This method efficiently converts shrimp shells into aerogels, yielding 200 kg of aerogels per ton of shrimp shells. – The 250 kg product significantly improves resource utilization compared to traditional chitin extraction processes and effectively avoids leachate and SO2 and NOx emissions from landfilling or incineration. x This process avoids the emission of harmful gases. In the preparation process, food-grade L-ascorbic acid is used instead of toxic reducing agents, and only low-toxicity reagents such as deionized water and methanol are used throughout. Furthermore, the methanol is recyclable, eliminating the environmental risks associated with organic solvents in traditional processes. The resulting aerogel mainly consists of BC400, PVA, and a small amount of rGO. BC400 and PVA are biodegradable in the natural environment (degradation rate exceeds 60% within six months), and rGO can also be recycled, thus avoiding secondary pollution throughout the material's life cycle and aligning with the development direction of green chemistry. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the preparation process of the present invention; Figure 2 This is a graph showing the adsorption data of diazepam according to the present invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0022] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0023] Refer to the instruction manual. Figure 1-2 ; A method for preparing shrimp shell aerogel includes the following steps: (1) Preparation of shrimp shell biochar (BC400) Shrimp shell biomass was washed three times with distilled water, drained, and dried at 60 °C for 12 h. The dried shrimp shells were then pulverized and transferred to a muffle furnace. Under an oxygen atmosphere, the temperature of the muffle furnace was increased from 30 °C to 400 °C at a heating rate of 10 °C / min for pyrolysis modification, and the temperature was maintained for 120 min. The resulting biochar was passed through a 200-mesh sieve (0.074 mm) and named BC400.

[0024] (2) In-situ reduction preparation of rGO solution Weigh 0.3 g of graphene oxide (GO) and 0.3 g of L-ascorbic acid, and dissolve them together in 30 mL of distilled water. React the mixture at 80 °C for 90 min, adding distilled water every 30 min to maintain a total reaction volume of 30 mL. After the reaction is complete, cool the product to room temperature to obtain a reduced graphene oxide (rGO) solution.

[0025] (3) BC400 / rGO 4:1 Preparation of composite solutions Weigh 1.2 g of the BC400 powder prepared in step (1) and add it to all the rGO solution in step (2). Place the mixture in a 50 mL centrifuge tube and vortex at 2500 r / min for 5 min for initial dispersion. Then, continue sonication in a constant temperature water bath at 25 °C using an ultrasonic cell disruptor (working frequency 100 Hz) for 30 min with an ultrasonic power of 280–320 W. Finally, obtain a BC400 / rGO with a biochar to reduced graphene oxide mass ratio of 4:1, which is uniformly and stably dispersed. 4:1 Composite solution.

[0026] (4) PVA / SC 5:1 Preparation of crosslinking solution Weigh 10.0 g of polyvinyl alcohol (PVA) powder and dissolve it in 200 mL of deionized water. Stir magnetically at 400 rpm for 1 h in an 80 ℃ water bath until the PVA is completely dissolved, yielding a transparent, viscous solution with a concentration of 50 g / L. After cooling the solution to room temperature, add 20 mL of a 10% (w / v) sodium citrate (SC) aqueous solution. Then, continue stirring the mixture magnetically at 400 rpm for 3 h at 60 ℃ to ensure complete reaction between SC and PVA, obtaining a PVA / SC mixture. 5:1 Cross-linked mixed solution.

[0027] (5) Preparation of glutaraldehyde (GA) crosslinking mixture The following components were mixed sequentially by volume: 47.14 mL glutaraldehyde (50%), 20 mL methanol, 20 mL glacial acetic acid, 2 mL concentrated sulfuric acid (98%), and 150 mL deionized water. After thorough mixing, the resulting solution was stored in a brown glass bottle away from light and used as an acidic catalytic crosslinking agent.

[0028] (6) BC400 / rGO 4:1 @SBA Composite Shrimp Shell Aerogel Molding and Post-processing Accurately measure 1.25 mL of BC400 / rGO. 4:1 The composite solution with 1.25 mL PVA / SC 5:1 The solution was mixed in a 10 mL beaker. The mixture was stirred at 600 rpm for 2 min on a magnetic stirrer to form a uniform black sol. Then, 1.37 mL of the glutaraldehyde crosslinking mixture prepared in step (5) was precisely added to the sol, and the mixture was stirred at 600 rpm for 3 min to complete the crosslinking reaction. The resulting crosslinked sol was quickly injected into a food-grade silicone mold and immediately placed in an ultra-low temperature freezer at -80 °C for 1 h to achieve physical freeze-thaw crosslinking and promote complete solidification of the system. Subsequently, the solidified sample was quickly transferred to a freeze dryer and freeze-dried at -80 °C and 0.1 mbar vacuum for 16 h to allow the ice crystal template to fully sublimate, finally obtaining BC400 / rGO with a three-dimensional porous network structure. 4:1 @SBA Composite Shrimp Shell Aerogel.

[0029] Specifically, the key process parameter should be controlled at a BC400 pyrolysis temperature of 390°C. – 410 ℃, rGO reaction temperature 78 – 82℃, ultrasonic power 280 – 320W, freezing temperature -78℃ – 82 ℃, freeze-drying vacuum degree 0.08 –0.12 mbar was used to ensure the consistency of the product structure and the stability of its performance.

[0030] The obtained BC400 / rGO 4:1 @SBA composite shrimp shell aerogel has a hierarchical pore structure with complementary micropores (≤2 nm), mesopores (2–50 nm), and macropores (≥50 nm), and a specific surface area ≥100 m². 2 With a porosity ≥85% and compressive strength ≥0.3 MPa, this composite shrimp shell aerogel achieves specific adsorption of diazepam through the synergistic effect of BC400 surface functional groups, rGO layered structure, and PVA / SC crosslinking network. It is particularly suitable for the adsorption and removal of diazepam from water, and can be used at pH 5. – 7. Temperature 20 – At 30 ℃, 10 – Adsorption removal was achieved using 1000 ng / L diazepam. After adsorption saturation, 5% [a specific solution was used]. – 30% methanol aqueous solution at 25℃ – Desorption at 30℃ for 40 min – With a desorption rate of ≥75% after 60 minutes, it can be recycled more than 3 times and is suitable for use in aquaculture and surface water removal of diazepam.

[0031] Data Comparison: Diazepam, a typical benzodiazepine, poses a significant ecological risk if it remains in the aquatic environment. The BC400 / rGO prepared according to this invention has a three-dimensional porous network structure. 4:1 Using SBA composite shrimp shell aerogel as the adsorbent, diazepam concentration gradients (100, 200, 500, 800, 1000 ng / L) were set up to investigate its adsorption efficiency. Figure 2 It can be seen that when the adsorption concentration is 100 ng / L, 200 ng / L and 500 ng / L, the adsorption efficiency of the shrimp shell aerogel of the present invention for diazepam does not have a significant statistical difference and remains above 80%. As the diazepam concentration increases to 800 ng / L, the adsorption sites gradually become saturated, but the adsorption efficiency is still about 70%. When the adsorption concentration is further increased to 1000 ng / L, the adsorption sites are close to complete saturation and the adsorption efficiency is about 60%.

[0032] The above description constitutes an embodiment of the present invention. The foregoing descriptions are preferred embodiments of the present invention. Unless there is a clear contradiction or a prerequisite for a particular preferred embodiment, the preferred embodiments can be arbitrarily combined and used. The embodiments and specific parameters described are merely for clearly illustrating the verification process of the invention and are not intended to limit the scope of patent protection of the present invention. The scope of patent protection of the present invention is still determined by its claims. Similarly, any equivalent structural changes made based on the description and drawings of the present invention should also be included within the scope of protection of the present invention.

Claims

1. A method for preparing shrimp shell aerogel, characterized in that, Includes the following steps: (1) Preparation of shrimp shell biochar BC400: Shrimp shell biomass was washed, dried, pulverized, and transferred to a muffle furnace for pyrolysis modification to obtain biochar BC400. (2) In-situ reduction preparation of rGO solution: Graphene oxide was reacted with L-ascorbic acid at 78–82 °C for 90 min. After the reaction was completed, the product was cooled to room temperature to obtain a reduced graphene oxide rGO solution. (3) BC400 / rGO 4:1 Preparation of the composite solution: After mixing BC400 biochar powder with rGO solution, the mixture was subjected to vortexing at 2500 r / min for 5 min and ultrasonication at 100 Hz for 30 min to obtain a BC400 / rGO mixture with a biochar to reduced graphene oxide mass ratio of 4:1, which was uniformly and stably dispersed. 4:1 Composite solution; (4) PVA / SC 5:1 Preparation of crosslinking solution: Polyvinyl alcohol (PVA) powder was dissolved in deionized water, and then a 10% (w / v) sodium citrate (SC) aqueous solution was added to react and obtain PVA / SC. 5:1 Cross-linked mixed solution; (5) Preparation of glutaraldehyde-GA crosslinking mixture: Mix 50% glutaraldehyde, methanol, glacial acetic acid, 98% concentrated sulfuric acid, and deionized water thoroughly and store in a brown glass bottle away from light. Use as an acidic catalytic crosslinking agent. (6) BC400 / rGO 4:1 @SBA Composite Shrimp Shell Aerogel Molding and Post-processing: BC400 / rGO 4:1 Composite solution with PVA / SC 5:1 The solutions were mixed, and then the acidic catalytic crosslinking agent mixture prepared in step (5) was added. The resulting crosslinking sol was stirred, molded, and frozen at -80 ℃ for 1 h. Then it was freeze-dried at -80 ℃ and 0.1 mbar for 16 h to obtain BC400 / rGO with a three-dimensional porous network structure. 4:1 @SBA Composite Shrimp Shell Aerogel.

2. The method for preparing shrimp shell aerogel according to claim 1, characterized in that, The specific steps (1) are as follows: after washing the shrimp shell biomass three times with distilled water, the water is filtered out and dried at 60 ℃ for 12 h. The dried shrimp shell biomass is crushed and transferred into a muffle furnace. Under an oxygen atmosphere, the temperature of the muffle furnace is increased from 30 ℃ to 400 ℃ at a heating rate of 10 ℃ / min for pyrolysis modification and kept at the temperature for 120 min. After cooling, the obtained biochar is passed through a 200-mesh sieve and named BC400.

3. The method for preparing shrimp shell aerogel according to claim 1, characterized in that, The specific steps (2) are as follows: Weigh 0.3 g of graphene oxide and 0.3 g of L-ascorbic acid, dissolve them together in 30 mL of distilled water, and react the mixed solution at 80 °C for 90 min. During the reaction, add distilled water every 30 min to maintain the total volume of the reaction system at 30 mL. After the reaction is completed, cool the product to room temperature to obtain a reduced graphene oxide rGO solution.

4. A method for preparing shrimp shell aerogel according to claim 1, characterized in that, Step (3) specifically involves: weighing 1.2 g of the BC400 biochar powder prepared in step (1) and adding it to all the rGO solution in step (2). The mixture is placed in a 50 mL centrifuge tube and vortexed vertically at 2500 r / min for 5 min for initial dispersion. Subsequently, it is subjected to ultrasonic cell disruption at 100 Hz in a constant temperature water bath at 25 °C for 30 min to obtain a BC400 / rGO mixture with a biochar to reduced graphene oxide mass ratio of 4:1 that is uniformly and stably dispersed. 4:1 Composite solution.

5. A method for preparing shrimp shell aerogel according to claim 1, characterized in that, Step (4) specifically involves: weighing 10.0 g of polyvinyl alcohol (PVA) powder, dissolving it in 200 mL of deionized water, and magnetically stirring at 400 rpm for 1 h in an 80 ℃ water bath until completely dissolved, resulting in a transparent viscous solution with a concentration of 50 g / L. After the solution cools to room temperature, add 20 mL of a 10% (w / v) sodium citrate (SC) aqueous solution. Then, continue magnetically stirring the mixed solution at 400 rpm for 3 h at 60 ℃ to allow SC and PVA to react fully, obtaining PVA / SC. 5:1 Cross-linked mixed solution.

6. A method for preparing shrimp shell aerogel according to claim 1, characterized in that, The specific step (5) is as follows: mix the following components in the following order by volume: 47.14 mL of glutaraldehyde with a mass fraction of 50%, 20 mL of methanol, 20 mL of glacial acetic acid, 2 mL of concentrated sulfuric acid with a mass fraction of 98% and 150 mL of deionized water. After mixing evenly, place the resulting solution in a brown glass bottle and store it in the dark for use as an acidic catalytic crosslinking agent.

7. A method for preparing shrimp shell aerogel according to claim 1, characterized in that, Step (6) specifically involves measuring 1.25 mL of BC400 / rGO. 4:1 The composite solution with 1.25 mL PVA / SC 5:1 The solution was mixed in a 10 mL beaker and stirred at 600 rpm for 2 min on a magnetic stirrer to form a uniform black sol. Then, 1.37 mL of the acidic catalytic crosslinking agent mixture prepared in step (5) was added to the sol, and stirring was continued at 600 rpm for 3 min to complete the crosslinking reaction. The resulting crosslinked sol was injected into a food-grade silicone mold and immediately placed in an ultra-low temperature freezer at -80 °C for 1 h to achieve physical freeze-thaw crosslinking and promote complete solidification. The solidified sample was then quickly transferred to a freeze dryer and freeze-dried at -80 °C and 0.1 mbar vacuum for 16 h to allow the ice crystal template to fully sublimate, finally obtaining BC400 / rGO with a three-dimensional porous network structure. 4:1 @SBA Composite Shrimp Shell Aerogel.

8. An application of shrimp shell aerogel, characterized in that, BC400 / rGO with a three-dimensional porous network structure prepared according to the preparation method of any one of claims 1-7 4:1 Application of @SBA composite shrimp shell aerogel in diazepam adsorption.